2015
DOI: 10.1016/j.ajpath.2015.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Novel Rat Model for Neurocysticercosis Using Taenia solium

Abstract: Neurocysticercosis is caused by Taenia solium infecting the central nervous system and is the leading cause of acquired epilepsy and convulsive conditions worldwide. Research into the pathophysiology of the disease and appropriate treatment is hindered by lack of cost-effective and physiologically similar animal models. We generated a novel rat neurocysticercosis model using intracranial infection with activated T. solium oncospheres. Holtzman rats were infected in two separate groups: the first group was inoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 40 publications
0
63
2
5
Order By: Relevance
“…In our study, all infected animals showed ependymitis, meningitis and perivasculitis. These alterations have also been described in experimental NCC in rats 19 . In our study, it was not possible to observe calcification of the cysticerci, or in the surrounding host tissue.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In our study, all infected animals showed ependymitis, meningitis and perivasculitis. These alterations have also been described in experimental NCC in rats 19 . In our study, it was not possible to observe calcification of the cysticerci, or in the surrounding host tissue.…”
Section: Discussionmentioning
confidence: 73%
“…In this model, the infected animals presented with tissue alterations and lesions such as encephalitis, perivasculitis, ventriculomegaly, ependymitis, meningitis, microgliosis accompanied by the parasite's death, and extraparenchymal and parenchymal inflammatory infiltration 6,18 . Other experimental models have been proposed but instead of using T. crassiceps cysticerci they performed an intracranial inoculation of T. solium oncospheres in rats 19 and in swine 20 . The rat NCC model reported that the infected animals presented with epilepsy, inflammatory infiltration, perivascular infiltrate, angiogeneses, spongy changes and mass effect in the brain tissue 19 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the viability and infectivity of the PO forms, 15 day old Hotzman rats, purchased from Universidad Peruana Cayetano Heredia (UPCH), Lima, Peru, were infected intracranially (in the bregma) as described by Verastegui [16] with 15 and 30 day old PO forms. Rats were anaesthetized with ketamine (100 mg/kg body weight) and xylazine (5 mg/kg body weight) before infection.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Verastegui et al., (2015) did not find any significant difference in number of cysts developed in the brain in young rats (10‐26 days) injected with variable numbers of activated T. solium oncospheres by extraparenchymal or intraparenchymal routes. The majority of cysts (80%) were viable with vesicular appearance.…”
Section: Animal Models For Neurocysticercosismentioning
confidence: 95%